2006
DOI: 10.1042/bj20060895
|View full text |Cite
|
Sign up to set email alerts
|

The differential catalytic activity of ribosome-inactivating proteins saporin 5 and 6 is due to a single substitution at position 162

Abstract: Saporin, a type I ribosome-inactivating protein produced by the soapwort plant Saponaria officinalis belongs to a multigene family that encodes its several isoforms. The saporin seed isoform 6 has significantly higher N-glycosidase and cytotoxic activities compared with the seed isoform 5, although the two have identical active sites. In the present study, we have investigated the contribution of non-conservative amino acid changes outside the active sites of these isoforms towards their differential catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…In fact, Asn 162 lies in close proximity to three hydrophobic residues, Phe 149 , Ala 151 and Val 153 . The negative charge of the N162D substitution may affect the stability of the active cleft by introducing a local structural change [21]. …”
Section: Saporin-s6mentioning
confidence: 99%
“…In fact, Asn 162 lies in close proximity to three hydrophobic residues, Phe 149 , Ala 151 and Val 153 . The negative charge of the N162D substitution may affect the stability of the active cleft by introducing a local structural change [21]. …”
Section: Saporin-s6mentioning
confidence: 99%
“…However, recent works have *Address correspondence to this author at the Institute of Biostructures and Bioimaging, CNR, Via Mezzocannone, n. 16. I-80134 Napoli, Italy; Tel: ++390812534507; Fax: ++390812536642; E-mail: rita.berisio@unina.it shown that DNase activity is observed even for highly pure RIPs [6,20,21] and that reduction in N--glycosidase activity results in a reduction of DNase activity [20], reinforcing the concept that RIPs act as N-glycosidases and as DNases using the same catalytic site [22].…”
Section: Introductionmentioning
confidence: 73%
“…The catalytic efficiency ( k cat / K m ) is 3.8 × 10 7 M −1 s −1 , which is ∼3.7-fold lower than values reported for RTA catalysis. 24 However, quantitation of the release of adenine from rabbit rRNA reveals that saporin L3 can depurinate up to 290 adenines/mol from rabbit rRNA (not shown). Moreover, saporin L3 also releases adenine from tRNA and luciferase mRNA at physiological pH.…”
Section: Resultsmentioning
confidence: 99%